FACTORS ASSOCIATED WITH NON-COMPLIANCE TO BRACING IN CLUB FOOT AMONG MOTHERS OF CHILDREN UNDER FIVE YEARS WITH CLUB FOOT IN AFRICAN INLAND CHURCH CURE INTERNATIONAL CHILDREN'S HOSPITAL, KIJABE, KENYA - Muinde, Winfred Ndinda; Kikuvi, Professor Gideon Mutie; Mutai, Dr. Joseph (Journal of Health, Medicine and Nursing, 2019)
Purpose: The study sought to determine factors associated with non-compliance to bracing in clubfoot management among children under five years in AIC Cure International Children's Hospital, Kijabe, Kenya. Methodology: The study adopted a cross-sectional descriptive design. It was carried out at AIC Cure International Children's Hospital, Kijabe, Kenya between April and August 2018. Both qualitative and quantitative methods were employed using a sample size of 174 participants. A semi-structured pre-tested questionnaire was used to collect data. Further, two focused group discussions were conducted, comprising of mothers with different characteristics. Quantitative data was entered for analysis using SPSS version 23.0. Descriptive, bivariate for example Chi square and multivariate for example regression statistical analysis was performed. Qualitative data from questionnaires was analysed through textual summaries was categorized and coded to match specific relevant research questions while data from FGDs was analysed using verbatim and a three-stage thematic approach. Presentation was done through frequencies, percentages, tables and charts. Results: The proportion of non-compliance to bracing was 16.8%, and the cases of non-compliance to bracing were mostly reported in male children (89.3%), and mostly among children aged between 1-2 years of age (35.7%). Majority of the mothers (92.9%) received support from health professionals during the treatment. Gender of the child had a significant association with non-compliance with mothers of male children having 89.3% non-compliance as opposed to 10.7% non-compliance of mothers with female children. Majority of those who did not comply to bracing (81.2%) had college/university education and above. Distance to health facility, inability to meet transport costs and gender of the child had significant association with non-compliance to bracing. Unique contribution to Theory, Practice and Policy: There is need to empower local facilities that is level 1 and level 2 to be able to manage conditions like clubfoot in order to avoid relapse or even permanent disability due to non-compliance. There is also need for detailed parent education on clubfoot bracing and importance of parent compliance.